Wayang-based digital storytelling: a project to promote students" collaborative and digital literacy skills - Kurniawan, Franky; Fitriani, Ika; Hendri, Zulfi; kasiyan, Kasiyan (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Indonesian Wayang is a cultural heritage recognized by UNESCO that must be preserved and passed toward future generations. One of the efforts to maintain wayang existence is through the insertion within educational field by the help of technology and animation in the form of digital storytelling. This research is aimed at exploring the implementation of wayang-based digital storytelling project at an Indonesian school which combined art, culture, skills, character education, cultural heritage values and global knowledge. The researchers applied narrative inquiry design in order to investigate and have in depth exploration toward the implementation of wayang-based digital storytelling within the researcher’s classroom. After having the analysis and reflection toward teaching and learning process as well as teaching documentation, it is concluded that the wayang-based project is potential to help students in addressing cultural challenges. Through the wayang media applied, the young generation know and increase their awareness to preserve the local cultural heritage. Further, the implementation of project in group using technology integration is concluded to be effective to enhace students’ collaborative, communicative, and ICT literacy which is very important in the 21 century era. Moreover, the topic which was close to socio environmental issues is expected to raise students’ awareness to be active individual to protect the surroundings. In conclusion, the application of wayang-based project within the classroom is effective and potential to strengthen Profil Pelajar Pancasila character stated in national curriculum (Kurikulum Merdeka).